2018
DOI: 10.55374/jseamed.v2i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Core Muscles Activation and the 400-Meter Overground Sprinting Velocity in Wheelchair Racers

Abstract: Objective: To measure the activity of the core muscles and the middle trapezius in T54 class wheelchair racers during full-effort over ground sprinting and to determine its association with propulsion velocity. Material and Method: Eightmale international wheelchair racershaving normal upper limband partial to normaltrunk function(T54 class athletes) propelled their racing wheelchairs on 400-m competition trackwith maximal effort. Electromyography(EMG)of the rectus abdominis (RA), iliocostalis lumborum (IL), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The results of the present study ( Table 5 ) showed that, in comparison with EMG variables of the rectus abdominis, only propulsion speed at R-RMS was correlated with erector spinae, which is consistent with Kumnerddee et al.’s (2018) findings. This study found no correlation between the back muscle group of the trunk and propulsion speed ( Kumnerddee et al., 2018 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results of the present study ( Table 5 ) showed that, in comparison with EMG variables of the rectus abdominis, only propulsion speed at R-RMS was correlated with erector spinae, which is consistent with Kumnerddee et al.’s (2018) findings. This study found no correlation between the back muscle group of the trunk and propulsion speed ( Kumnerddee et al., 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study ( Table 5 ) showed that, in comparison with EMG variables of the rectus abdominis, only propulsion speed at R-RMS was correlated with erector spinae, which is consistent with Kumnerddee et al.’s (2018) findings. This study found no correlation between the back muscle group of the trunk and propulsion speed ( Kumnerddee et al., 2018 ). In the present study, the correlation between rectus abdominis EMG activity and propulsion speed at multiple time points suggests that athletes encounter greater resistance when trunk overcoming flexion than when trunk overcoming raising.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations